The Key English Pronunciation Difficulties for Egyptian EFL Learners - Hasnaa Hasan Sultan Abdelreheem (Anglica. An International Journal of English Studies, 2023)
Despite all the attempts by ESL and EFL learners to attain (near-)native proficiency, many phonological, lexical and spelling mistakes still occur in any L2 learning environment (Huwari 2019, 31). This paper aims to investigate the key English pronunciation difficulties, both segmental (on the level of speech sounds) and suprasegmental (rhythm, stress, and juncture), of Egyptian learners of English, in a corpus of audio and/or video recordings of English conversation and presentation skills classes by Egyptian university students who are also native speakers of Egyptian Colloquial Arabic (ECA). The project involves both contrastive analysis (of the phonological systems of English, Egyptian Arabic and Modern Standard Arabic) as well as error analysis. While the significance of contrastive analysis lies in helping EFL teachers predict the problematic aspects (Al-Saqqaf and Vaddapalli 2012, 56), error analysis would provide them with the actual problems encountered by the learners and the extent of their seriousness.